The Effect Of Retention Factors On Organisational Commitment: An Investigation Of High Technology Employees - Andreas Dockel (SA Journal of Human Resource Management, 2006)
The objective of the present study was to investigate specific retention factors that induced the organisational commitment of high technology employees. A sample of 94 professional technicians from a South African owned telecommunications company based in the Gauteng province participated. The Organisational Commitment Scale and a retention factor measurement scale were administered. The most relevant explanatory factors were compensation, job characteristics, supervisor support, and work/life policies, which appeared to have a statistically significant influence on the development of organisational commitment in high technology employees. The implications of the findings are discussed.